Knowing yourself and your partner: accuracy of personality judgment in recently cohabiting couples - Bühler, Janina Larissa; Scheling, Louisa; Wrzus, Cornelia (Journal of personality and social psychology, 2025)
Big Five personality traits and states are positively associated with each other. However, most of this knowledge is based on intrapersonal perception (i.e., either self- or partner reports), and little is known about the associations based on interpersonal perception (i.e., combining self- and partner reports). Such knowledge, however, would be crucial in understanding how accurately close others (e.g., romantic partners) perceive each other’s personality in general and daily life. Therefore, the goal of this study was to comprehensively test the trait-state associations, using self- and partner reports, to better understand accuracy of personality judgment among couples. Moreover, to learn about the conditions of better or worse accuracy in personality judgment, we examined the moderating roles of relationship satisfaction and situational factors. Data came from 292 recently cohabiting couple members (M = 25.41 years) who participated in a preregistered experience-sampling study, providing up to 50 personality-state assessments over 10 days. The findings from multilevel models supported previous knowledge on intrapersonal perception and significantly expanded the knowledge on interpersonal perception. Specifically, the findings suggested the most robust pattern for conscientiousness and neuroticism, ascribing these Big Five domains a significant role among recently cohabiting couples. Interestingly, accuracy was not enhanced among more satisfied couple members, but it was largely facilitated when partners were exclusively together as a couple (vs. with other people). Overall, this research shows that the use of multiple sources allows for a more comprehensive understanding of personality, especially when the aim is to understand the accuracy of personality judgment in couples. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 24.02.2026